H24

So sánh A và B

A = \(\frac{20^{10}+1}{20^{10}-1}\)Và   B = \(\frac{20^{10}-1}{20^{10}-3}\)

DP
16 tháng 4 2017 lúc 6:05

Ta có:

\(A=\frac{20^{10}+1}{20^{10}-1}=1\)

\(B=\frac{20^{10}-1}{20^{10}-3}=1\)

Vậy A và B bằng nhau

Bình luận (0)
TQ
16 tháng 4 2017 lúc 6:07

Tính A và B rồi ta so sánh:

A = \(\frac{20^{10}+1}{20^{10}-1}\) = \(1\)

B = \(\frac{20^{10}-1}{20^{10}-3}\) = \(1\)

Mà \(1\) = \(1\)

Nên: A = B

Bình luận (0)
ZI
16 tháng 4 2017 lúc 6:12

A=(20^10+1/20^10-1)=(20^10-1+2/20^10-1)=(20^10-1/20^10-1)+(2/20^10-1)=1+(2/20^10-1).

Tương tự ,B=1+(2/20^10-3).
Vì 2/20^10-1>2/20^10-3(vì 20^10-1>20^10-3).

=>A<B.

Vậy A<B.

tk mk nha đúng 1000000%,2b bạn kia sai rùi

Bình luận (0)
H24
16 tháng 4 2017 lúc 9:26

ta co A=\(\frac{20^{10}+1}{20^{10}-1}=\frac{20^{10}-1+2}{20^{10}-1}=\frac{20^{10}-1}{20^{10}-1}+\frac{2}{20^{10}-1}\)=\(1+\frac{2}{20^{10}-1}\)

        B=\(\frac{20^{10}-1}{20^{10}-3}=\frac{20^{10}-3+2}{20^{10}-3}=\frac{20^{10}-3}{20^{10}-3}+\frac{2}{20^{10}-3}=1+\frac{2}{20^{10}-3}\)

ta thấy\(20^{10}-1>20^{10}-3\) suy ra \(\frac{2}{20^{10}-1}< \frac{2}{20^{10}-3}\)vậy A<B

Bình luận (0)